2019
DOI: 10.24330/ieja.586838
|View full text |Cite
|
Sign up to set email alerts
|

Some Remarks on the Order Supergraph of the Power Graph of a Finite Group

Abstract: Let G be a finite group. The main supergraph S(G) is a graph with vertex set G in which two vertices x and y are adjacent if and only if o(x)|o(y) or o(y)|o(x). In an earlier paper, the main properties of this graph was obtained. The aim of this paper is to investigate the Hamiltonianity, Eulerianness and 2-connectedness of this graph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Motivated by the work of Kelarev and Quinn, Chakrabarty et al considered undirected power graphs (power graph for short) of semigroups [8]. In recent years, there has been considerable interest to the study of power graphs, but the second graph introduced very recently by the present authors [19,20]. In [19], the authors focused on the relationship between power graph and its main supergraph and some basic properties of this graph are studied.…”
Section: Power Graph Of Finite Groups: a Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the work of Kelarev and Quinn, Chakrabarty et al considered undirected power graphs (power graph for short) of semigroups [8]. In recent years, there has been considerable interest to the study of power graphs, but the second graph introduced very recently by the present authors [19,20]. In [19], the authors focused on the relationship between power graph and its main supergraph and some basic properties of this graph are studied.…”
Section: Power Graph Of Finite Groups: a Literature Reviewmentioning
confidence: 99%
“…In recent years, there has been considerable interest to the study of power graphs, but the second graph introduced very recently by the present authors [19,20]. In [19], the authors focused on the relationship between power graph and its main supergraph and some basic properties of this graph are studied. In [20], the automorphism group of this graph in general are computed, but this paper devotes to the study of graph eigenvalues of main supergraph.…”
Section: Power Graph Of Finite Groups: a Literature Reviewmentioning
confidence: 99%
“…In [22], Ma and Su studied the independence number of an order graph. Hamiltonianity and Eulerianness of S (G) were investigated in [12] and spectrum and L-spectrum of S (G) were investigated in [11]. In [3], Asboei and Salehi studied the well-known Thompson's problem and recognized the projective special linear groups and the projective linear groups by their order graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hamzeh and Ashrafi [14] studied some properties of the order supergraph, and in particular, they showed that S(G) = P(G) if and only if G is cyclic. Also, in [15], they investigated Hamiltonianity, Eulerianness and 2-connectedness of this graph.…”
Section: Introductionmentioning
confidence: 99%